Analisis penyebab demurrage pada proses bongkar muat material impor proyek kapal x dengan metode six sigma DMAIC (Studi kasus: PT ABC) - Wandana, Yasmine Azalia; Rahmawati, Nur (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT ABC is one of the industry that produce ships. In the production of Ship X, PT ABC needs imported materials sent from other country. In the process of loading and unloading these materials, PT ABC encounters operational difficulties that cause demurrage. This study aims to identify the causes of demurrage and provide suggestions for improvements to minimize the occurrence of demurrage in the next loading and unloading process. The method used in this research is the six sigma method which consists of five stages, namely define, measure, analyze, improve, and control. The results showed that there were 10 causes of demurrage in the loading and unloading process of Ship X materials during 2022. In addition, there are 3 most dominant causes of demurrage, namely late receipt of documents (36.84%), document discrepancies (15.79%), and waiting for the signature of related parties (10.53%). The recommended actions to minimize the occurrence of demurrage include implementing more efficient SOP and improving communication between internal and external stakeholders.